“Everybody is their own Island”: Teacher Disconnection in a Virtual School - Hawkins, Abigail; Barbour, Michael K.; Graham, Charles R. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2012)
Virtual schooling is a recent phenomenon in K-12 online learning. As such, the roles of the online teachers are emerging and differ from those of the traditional classroom teacher. Using qualitative interviews of eight virtual high school teachers, this study explored teachers’ perceptions of their online teaching role. Teachers expressed a sense of disconnection from their students, the profession, and their peers as a result of limited interactions due to significant institutional barriers. Researchers discuss the implications of this disconnection as well as future avenues for research.